PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. XYZ ROKAN HULU PROVINSI RIAU - Sandora, Meri; Permadani, Via Ayu (Eko dan Bisnis: Riau Economic and Business Review, 2021)
PT. XYZ Rokan Hulu Riau Province in terms of production is still not good and has not reached the predetermined target. Then in the training variable, the problem is that the instructor is not able to invite active participants to discuss the training material. While the work environment variable the problem is the condition of the work environment that is less comfortable. This research was conducted at PT. XYZ Rokan Hulu Riau Province. The purpose of this study was to determine partially and simultaneously between training and work environment on employee performance at PT. XYZ Rokan Hulu Riau Province. Respondents in this study amounted to 92 people. This research is descriptive quantitative by using multiple linear regression test. Based on the results of the study showed that the training had a partial effect on the performance of employees at PT. XYZ Rokan Hulu Riau Province and the Work Environment partially affect the performance of employees at PT. XYZ Rokan Hulu Riau Province. Then Simultaneously, the variables of Training and Work Environment have a significant effect on employee performance variables at PT. XYZ Rokan Hulu Riau Province. The magnitude of the effect on performance is 68.1% while the rest (31.9%) is influenced by other variables not examined in this study.PT. XYZ Rokan Hulu Riau Province. Then Simultaneously, the variables of Training and Work Environment have a significant effect on employee performance variables at PT. XYZ Rokan Hulu Riau Province. The magnitude of the effect on performance is 68.1% while the rest (31.9%) is influenced by other variables not examined in this study. PT. XYZ Rokan Hulu Riau Province. Then Simultaneously, the variables of Training and Work Environment have a significant effect on employee performance variables at PT. XYZ Rokan Hulu Riau Province. The magnitude of the effect on performance is 68.1% while the rest (31.9%) is influenced by other variables not examined in this study